2014
DOI: 10.1091/mbc.e13-10-0609
|View full text |Cite
|
Sign up to set email alerts
|

α-Tubulin K40 acetylation is required for contact inhibition of proliferation and cell–substrate adhesion

Abstract: Acetylation of α-tubulin on lysine 40 is a mark of long-lived microtubules, but its function is elusive. Knocking out the tubulin acetyltransferase αTAT1 shows that α-tubulin K40 acetylation is critical for contact inhibition of proliferation. It is proposed that acetylated microtubules facilitate transport of the Hippo regulator Merlin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
83
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 69 publications
3
83
1
1
Order By: Relevance
“…This is one possible mechanism to ensure microtubule acetylation at the leading edge for promoting directional cell migration [129]. It was also reported that tubulin acetylation is required for cellcell contact inhibition and cell adhesion [51]. Decreased dynamics of acetylated microtubules induced by HDAC6 inhibition affects turnover of cellular focal adhesion [130].…”
Section: Tubulin Acetylation and Intracellular Transportmentioning
confidence: 98%
See 4 more Smart Citations
“…This is one possible mechanism to ensure microtubule acetylation at the leading edge for promoting directional cell migration [129]. It was also reported that tubulin acetylation is required for cellcell contact inhibition and cell adhesion [51]. Decreased dynamics of acetylated microtubules induced by HDAC6 inhibition affects turnover of cellular focal adhesion [130].…”
Section: Tubulin Acetylation and Intracellular Transportmentioning
confidence: 98%
“…They possess intrinsic a-tubulin acetyltransferase activity [47,48]. Moreover, ATAT1 functions as a bona-fide tubulin acetyltransferase in vivo, because deletion of the mouse gene leads to nearly complete loss of tubulin acetylation in embryos and various tissues [49][50][51]. Thus, ATAT1 is now considered as a major tubulin acetyltransferase in mammals.…”
Section: Tubulin Acetyltransferases and Deacetylases Identification Amentioning
confidence: 99%
See 3 more Smart Citations